Teeth re-whitening effect of strawberry juice on coffee stained teeth - Pramesti, Annisya; Jasrin, Tadeus Arufan; Hidayat, Opik Taofik (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2013)
Many people favor coffee. However, regarding health and aesthetic dentistry, coffee gives a negative effect. Tanin in coffee causes a brown stain on the tooth surface. Therefore, in aesthetic dental care, teeth whitening has become popular matter. One of the natural ingredients used for teeth whitening treatment is strawberry. The purpose of this study was to obtained data regarding the effect of strawberry juice on the re-whitening process of the coffee-stained tooth enamel surface. This study was a pure experimental in-vitro using Friedman and Wilcoxon Matched Pairs Tests for statistical analysis. The population of this study was anterior teeth. The samples were maxillary central incisors. The sampling technique using sample size determination based on the testing formulas of the difference of two average data pairs resulted in 11 specimens. The result of the research showed that all coffee-stained teeth sample had an increasing enamel colour index. The samples were then applied with strawberry juice resulted in a significant average difference colour index value indicated by p<0.001. The conclusion of this research indicated that there was an effect of strawberry juice on the coffee-stained teeth re-whitening process.